2017
DOI: 10.1039/c6cp06552j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structure and phase transition of a Xe–N2 compound at high pressure: experimental indication of orbital interaction between xenon and nitrogen

Abstract: The van der Waals compound Xe(N) with a C15 Laves structure was successfully synthesised at pressures greater than 4.4 GPa. We found that, at 10 GPa, the structure reversibly transforms from a cubic to a tetragonal phase. Further compression results in changes of Xe-N compound, which could result in the enhancement of orbital interactions between the xenon and nitrogen atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…For the following more than half a century, a great many experimentally pioneering works have opened the updated window for search of new Ng compounds in this field. A great number of chemically bound coumpounds containing lighter noble gas atoms (NGs) have been synthesized and characterized. It has also been reported that NGs can chemically bond to metal in forming noble gas–metal complexes. The M­(CO) 5 (M = Cr, Mo, W) are coordinated by one NG in forming the M­(CO) 5 (Ng) (Ng = Ar, Kr, Xe) complexes in noble gas matrixes. The of Fe­(CO) 5 reacts photochemically with Xe to form Fe­(CO) 4 (Xe) in supercritical liquid Xe solution .…”
Section: Introductionmentioning
confidence: 99%
“…For the following more than half a century, a great many experimentally pioneering works have opened the updated window for search of new Ng compounds in this field. A great number of chemically bound coumpounds containing lighter noble gas atoms (NGs) have been synthesized and characterized. It has also been reported that NGs can chemically bond to metal in forming noble gas–metal complexes. The M­(CO) 5 (M = Cr, Mo, W) are coordinated by one NG in forming the M­(CO) 5 (Ng) (Ng = Ar, Kr, Xe) complexes in noble gas matrixes. The of Fe­(CO) 5 reacts photochemically with Xe to form Fe­(CO) 4 (Xe) in supercritical liquid Xe solution .…”
Section: Introductionmentioning
confidence: 99%